Epidemiology and return to play following isolated syndesmotic injuries of the ankle: a prospective cohort study of 3677 male professional footballers in the UEFA Elite Club Injury Study. Issue 15 (21st December 2017) - Lubberts, Bart; D'Hooghe, Pieter; Bengtsson, Håkan; DiGiovanni, Christopher W; Calder, James; Ekstrand, Jan
Abstract : Aim: To determine the epidemiology of isolated syndesmotic injuries in professional football players. Methods: Data from 15 consecutive seasons of European professional football between 2001 and 2016 contributed to the dataset of this study. Match play and training data from a total of 3677 players from 61 teams across 17 countries have been included. Team medical staff recorded player exposure and time loss injuries. Injury incidence was defined as the number of injuries per 1000 player-hours. Injury burden was defined as number of days absence per 1000 player-hours. Seasonal trends for isolated syndesmotic injury incidence, isolated syndesmotic injury proportion of ankle ligament injuries and isolated syndesmotic injury burden were analysed via linear regression. Results: The isolated syndesmotic injury incidence was 0.05 injuries per 1000 hours of exposure (95% CI 0.04 to 0.06) or one injury per team every three seasons. The injury incidence during match play was 13 times higher compared with during training, 0.21 (95% CI 0.16 to 0.26) and 0.02 (95% CI 0.01 to 0.02), respectively. Out of the 1320 ankle ligament injuries registered during the 15 seasons, 94 (7%) were diagnosed as isolated syndesmotic injuries. An annual increase in injury incidence was observed (R 2 =0.495, b=0.003, 95% CI 0.001 to 0.004, P=0.003). However, no significant annual change of injury burden was observed (R 2 =0.033, b=0.032, 95% CI −0.073 to 0.138, P=0.520). Seventy-four per cent of the injuries were contact related, and the mean (±SD) absence following an isolated syndesmotic injury was 39 (±28) days. Conclusions: The incidence of isolated syndesmotic injuries in elite professional European football annually increased between 2001 and 2016.